IMPLEMENTATION OF VIRTUAL ANALYZERS IN THE CONTROL OF INDUSTRIAL TECHNOLOGICAL PROCESSES (International Conference on Education and Innovation, 2025)
In most practical cases, real-time control of technological processes is carried out based on the results of production monitoring.Monitoring, in turn, is implemented through the collection and preliminary processing of data obtained from measuring instruments and complexes, which are typically integrated into Automated Process Control Systems (APCS), as well as from laboratory analyses of intermediate and final products.Unfortunately, the results obtained from plant laboratory analyses usually lack the required completeness and timeliness. Practical experience shows that, in some cases, even their reliability is insufficient. The main reason for this lies in the mismatch between the throughput capacity and technological capabilities of laboratory analytical equipment and the actual needs of modern production systems.